Adsorption of 2,4-dichlorophenol from water using deep eutectic solvents-functionalized carbon nanotubes - Ibrahim, Rusul Khaleel; AlSaadi, Mohammed Abdulhakim; AlOmar, Mohamed Khalid; Ibrahim, Shaliza (Desalination Publications, 2018)
In this work, novel adsorbents for 2,4-dichlorphenol (DCP) were introduced using deep eutectic solvent (DES) as functionalization agent for multi-wall carbon nanotubes (MWCNTs). Choline chloride salt (ChCl) was mixed with ethylene glycol (EG) as hydrogen bond donor (HBD) at molar ratio of (1:2) to prepare DES. Three DES-based MWCNTs adsorbents were produced and their chemical, physical and morphological properties were investigated using, RAMAN, FTIR, FESEM, zeta potential, TGA, TEM and BET surface area. The capability of DES as non-destructive functionalization agent for MWCNTs was proved by the increase of the purity and the surface area of MWCNTs. Response surface methodology was used to define the optimum conditions for 2,4-DCP adsorption onto each adsorbent. The adsorption experimental data were well described by pseudo-second order kinetic mode land by Langmuir isotherm model. DES-acid treated MWCNTs showed the highest maximum adsorption capacity of 390.53 mg g −1 .